Genome-wide plant responses during the non-host interaction of tobacco with the Hemibiotrophic Bacterium Xanthomonas campestris pv. Vesicatoria - Pierella Karlusich, Juan J. (2017)
Fil: Fil: Pierella Karlusich, Juan J. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.